Indonesian Port Re-Service as the Main Support of the Supply Chain - Ratnawati, Elfrida; Nugraha, Andhyka Tyaz; Pandamdari, Endang (ExcelingTech, 2020)
Ports as key of transportation network, the gate of economy activities, transportational mode transition center, site of distribution, production, and consolidation of goods and services, and a place that highly related with routine industrial, agricultural, tourism, and commercial activities. Its important roles in commercial field are as chain of transportation (transportation system) which is a series of goods movement from sender to the receiver or customer that involves various of transportational mode transitions. Are the activities conducted related with supply and chain in ports are already in harmony from the perspective of regulations? Should these ports be re-serviced to improve its performance as a part of supply and chain management? The utilized method in this research is a normative method, with a descriptive analysis by utilizing secondary and primary data. The result of this research reveals that the implemented policy is not in harmony with the available resource in the field, and caused unoptimum output. Because of that, a cooperation between the available human resources in the policy implementation is vital to improve the sector’s contribution towards the national economy, where ports are placed as an accelerator of physical and economical development. Port reservice is a requirement to improve the inconducive and unprofessional Indonesian ports that contribute on ineffective and inefficient service performance. Indonesian ports should organize its performance by improving their tools as supporting facilities and infrastructures. If the available funding is insufficient, port management is recommended to invite both domestic or foreign investors to provide capital investments.